PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS TEACHING AT THE RIGHT LEVEL (TaRL) UNTUK KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MTs - Annisa Asma Azizah; Khusnul Safrina (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Students' mathematical communication skills are often not supported by teaching materials appropriate to their ability levels, making it difficult for them to understand the material. This study aims to develop a Teaching at the Right Level (TaRL)-based Student Worksheet (LKPD) for the topic of flat-sided geometric shapes in Phase D of Grade VIII. This research is a development study (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were Grade VIII students at MTsN 3 Banda Aceh. Data collection techniques included expert validation sheets for content and media, as well as practicality questionnaires for teachers and students. The results showed that the developed LKPD met the criteria for validity and practicality. Content validation obtained a percentage of 83.59%, while media validation reached 93.01%, both classified as highly valid. The practicality test by teachers resulted in a percentage of 92.50%, and by students, 88.13%, both categorized as highly practical. Based on these findings, the developed TaRL-based LKPD meets the criteria of being highly valid and highly practical, making it suitable for use in mathematics learning in schools/madrasahs.